What Drives E-Voting in Local Governments: Trust, Readiness, Accessibility, or Outcome Expectancy? - Zahra, Hanifah; Yuanda Daud, Vicko; Urumsah, Dekar (Jurnal Ilmiah Ekonomi Global Masa Kini, 2025)
This study aims to identify and analyze the key factors driving public acceptance of the electronic voting (e-voting) system at the local government level, particularly in Sleman Regency. This quantitative research extends the Technology Acceptance Model (TAM) by examining the effects of trust in the internet, trust in government, human resource readiness, accessibility, and outcome expectations on the acceptance of the e-voting system. Primary data were collected from 200 respondents through an online questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results of the structural model testing indicate that the five independent variables collectively explain 68.5% of the variance in the decision to use e-voting, demonstrating that the model has good predictive power. Specifically, Accessibility, Human Resource Readiness, and Outcome Expectation were found to have positive and significant effects on the intention to adopt e-voting. This suggests that public confidence in the practical benefits of the system (such as efficiency and transparency), along with their level of digital literacy readiness, are the main drivers of technology adoption. Meanwhile, Trust in Government and Trust in the Internet were found to have no significant effect in the early stage of adoption, emphasizing that in the context of new technologies in the public sector, perceived usefulness and user readiness play a more dominant role. The findings contribute theoretically to the extension of the TAM framework and practically suggest that e-voting implementation strategies should focus on enhancing digital literacy and effectively communicating the system’s benefits to the public. Keywords: Accessibility, E-Voting, Human Resource Readiness, Outcome Expectation, Trust.